Transcriptomic and epigenetic landscape of nimorazole-enhanced radiochemotherapy in head and neck cancer - Besso, María José; Bitto, Verena; Koi, Lydia; Wijaya Hadiwikarta, Wahyu; Conde-Lopez, Cristina; Euler-Lange, Rosemarie; Bonrouhi, Mahnaz; Schneider, Karolin; Linge, Annett; Krause, Mechthild; Baumann, Michael; Kurth, Ina (Radiotherapy and oncology, 2024)
Background - Hypoxia remains a challenge for the therapeutic management of head and neck squamous cell carcinoma (HNSCC). The combination of radiotherapy with nimorazole has shown treatment benefit in HNSCC, but the precise underlying molecular mechanisms remain unclear. - Purpose - To assess and to characterize the transcriptomic/epigenetic landscape of HNSCC tumor models showing differential therapeutic response to fractionated radiochemotherapy (RCTx) combined with nimorazole. - Materials/methods - Bulk RNA-sequencing and DNA methylation experiments were conducted using untreated and treated HNSCC xenografts after 10 fractions of RCTx with and without nimorazole. These tumor models (FaDu, SAS, Cal33, SAT and UT-SCC-45) previously showed a heterogeneous response to RCTx with nimorazole. The prognostic impact of candidate genes was assessed using clinical and gene expression data from HNSCC patients treated with primary RCTx within the DKTK-ROG. - Results - Nimorazole responder and non-responder tumor models showed no differences in hypoxia gene signatures However, non-responder models showed upregulation of metabolic pathways. From that, a subset of 15 differentially expressed genes stratified HNSCC patients into low and high-risk groups with distinct outcome. - Conclusion - In the present study, we found that nimorazole non-responder models were characterized by upregulation of genes involved in Retinol metabolism and xenobiotic metabolic process pathways, which might contribute to identify mechanisms of resistance to nitroimidazole compounds and potentially expand the repertoire of therapeutic options to treat HNSCC.
Gesehen am 14.02.2025